Dynamic model of vascular-targeted photodynamic therapy. Issue 10 (27th July 2017) - Hu, Xiao-ming; He, Linhuan; Zhao, Yi
Abstract: Vascular-targeted photodynamic therapy has shown efficiency in treating port wine stains. A dynamic model that incorporates blood flow, kinetic diffusion, oxygen and photosensitizer consumption and reaction, and light modulation is proposed to reveal the interactions among light, photosensitizer, and oxygen. Simulation results show that pulse light modulation synchronized with heartbeats hold the advantage of increased singlet oxygen accumulation, higher oxygen concentration and lower temperature. Meanwhile, constant light treatment is advantageous in terms of higher temperature, lower total oxygen concentration and singlet oxygen accumulation. Therefore, the optimized treatment protocol may involve a balance among the phototoxicity, hypoxia, and photothermolysis.